The Potential Benefits of Curcumin-Enriched Diets for Adults with Colorectal Cancer: A Systematic Review - María Neira; Constanza Mena; Keila Torres; Layla Simón (Antioxidants)
Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Conventional treatments such as chemotherapy and radiotherapy are often associated with severe side effects and limited effectiveness. Curcumin, a polyphenol derived from Curcuma longa, has demonstrated anti-inflammatory and anticancer properties. A systematic review of the recent scientific literature followed PRISMA guidelines to evaluate the benefits of a curcumin-enriched diet for adults with colorectal cancer. Articles published between 2018 and 2024 were retrieved from PubMed, SciELO, Google Scholar, and Scopus. Studies meeting the inclusion criteria focused on curcumin, adults, and colorectal cancer outcomes. The administration of curcumin-containing products was associated with improved survival rates, enhanced quality of life, tumor reduction, and anti-inflammatory effects. A curcumin-enriched diet shows potential as an effective adjunct therapy for CRC patients, though its limited bioavailability and potential side effects, such as gastrointestinal discomfort, pose challenges. Addressing these limitations through larger cohorts, extended study durations, and improved formulations to enhance bioavailability is essential. Such efforts could enable the development of personalized dietary recommendations for CRC management.